Reports on the discovery of Peru - Markham, Clements R. (New York : Cambridge University Press, 2010)
The publications of the Hakluyt Society (founded in 1846) made available edited (and sometimes translated) early accounts of exploration. The first series, which ran from 1847 to 1899, consists of 100 books containing published or previously unpublished works by authors from Christopher Columbus to Sir Francis Drake, and covering voyages to the New World, to China and Japan, to Russia and to Africa and India. In this 1872 volume, Clements R. Markham, Honorary Secretary of the Society from 1858 to 1887, and then its President for twenty years, translated and edited four accounts of the Spanish conquest of Peru, written by eye-witnesses including Francisco Pizarro's secretary and his brother Hernando. The narratives include the events surrounding the downfall of the Inca empire; the final document is a notary's account of the distribution of the gold and silver which the Incas paid to the Spaniards as ransom for their ruler.
Keywords: History; History of the Americans